Effects of progesterone stimulated allopregnanolone on craving and stress response in cocaine dependent men and women - Milivojevic, Verica (Psychoneuroendocrinology, 2015)
OBJECTIVES: Fluctuations in progesterone levels during the menstrual cycle have been shown to affect physiological and subjective effects of cocaine. Furthermore, our laboratory has demonstrated that following drug-cue exposure, cocaine dependent women with high levels of circulating progesterone display lower diastolic and systolic blood pressure responses and report lower levels of anxiety and drug craving compared to cocaine dependent women with low levels of progesterone. In the current study we examined the role of the progesterone derived neuroactive steroid allopregnanolone (ALLO) on stress arousal, inhibitory control and drug craving in cocaine dependent subjects. METHODS: Plasma levels of ALLO were measured using GC/MS in 46 treatment-seeking cocaine dependent men and women on day 5 of a 7-day treatment regimen of micronized progesterone (15M / 8F) (400mg/day) or placebo (14M / 9F) administered in a double blind, randomized manner. As a control, levels of the testosterone derived neurosteroid androstanediol (ADIOL) were also measured. All subjects participated in laboratory sessions on days 5–7 of progesterone/placebo administration in which they were exposed to a series of 5-min personalized guided imagery of either a stressful situation, cocaine use or of a neutral setting and dependent variables including subjective craving, mood, Stroop task as a measure of inhibitory control performance and plasma cortisol were assessed. Participants were grouped by high or low ALLO level and levels of dependent variables compared between ALLO groups. RESULTS: Progesterone relative to placebo significantly increased ALLO levels with no sex differences. There were no effects of micronized progesterone on the testosterone derived ADIOL. Individuals in the high versus the low ALLO group showed decreased levels of cortisol at baseline, and a higher cortisol response to stress; higher positive mood scores at baseline and improved Stroop performance in the drug-cue and stress conditions, and reduced cocaine craving across all imagery conditions. CONCLUSIONS: As expected, cocaine dependent individuals administered progesterone showed significantly higher ALLO plasma levels. High levels of ALLO appeared to normalize basal and stress response levels of cortisol, decrease cocaine craving and also contribute to improvements in positive emotion and Stroop performance in response to stress and drug-cue exposures. These findings suggest that the neuroactive steroid ALLO plays a significant role in mediating the positive effects of progesterone on stress arousal, cognitive performance and drug craving in cocaine dependence.